2001
DOI: 10.1007/s00428-001-0551-3
|View full text |Cite
|
Sign up to set email alerts
|

CD34+ fibrocytes in neoplastic and inflammatory pancreatic lesions

Abstract: Besides its function as a matrix-producing cell, the CD34+ fibrocyte has been reported to be an antigen-presenting cell capable of priming naive T cells in situ. Therefore, it has been claimed that the CD34+ fibrocyte may play an important role in host response to tissue damage. The objective of the present study was to analyze the presence and distribution of CD34+ fibrocytes and smooth muscle actin (SMA) reactive myofibroblasts in relation to the underlying pancreatic disease. We investigated a total of 12 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 20 publications
3
67
0
Order By: Relevance
“…Already in 1994, Bucala et al [25] have identified a distinct leukocyte subpopulation, termed fibrocytes, exhibiting characteristics of both stem cells and myo-/fibroblasts. Various studies have confirmed the contribution of circulating fibrocytes to wound repair and fibrosis [26,27]. Mesenchymal stem cells represent a further BM-derived population with multilineage potential and their transition into myofibroblasts has been shown [24,28].…”
Section: Discussionmentioning
confidence: 94%
“…Already in 1994, Bucala et al [25] have identified a distinct leukocyte subpopulation, termed fibrocytes, exhibiting characteristics of both stem cells and myo-/fibroblasts. Various studies have confirmed the contribution of circulating fibrocytes to wound repair and fibrosis [26,27]. Mesenchymal stem cells represent a further BM-derived population with multilineage potential and their transition into myofibroblasts has been shown [24,28].…”
Section: Discussionmentioning
confidence: 94%
“…An interesting finding was the coexpression of CD34, CD117 and bcl-2 in stromal cells. CD34, a myeloid stem cell marker, is known to be expressed by fibrocytes in neoplastic and inflammatory pancreatic lesions 6 and seems to play an important role in maintaining stromal integrity and inhibition of tumor cell migration. 7 It is also observed in solitary fibrous tumors, which may occur in the pancreas.…”
Section: Resultsmentioning
confidence: 99%
“…+ fibrocytes (CD34 is a 110 kDa surface antigen selectively expressed on human haematopoietic progenitor cells) originating from myeloid precursors in the bone marrow were considered as a source of myofibroblasts in cancer of the colon [129], pancreas, [130], and breast [131]. Experimental studies have shown that CD34 + fibrocytes are attracted by the secondary lymphoid chemokine CCL-21, a ligand of the CCR7 chemokine receptor, and invade sites of tissue damage in vivo.…”
Section: The Origin Of Myofibroblastsmentioning
confidence: 99%